Cover Feature: Steric and Electronic Effects of Phosphane Additives on the Catalytic Performance of Colloidal Palladium Nanoparticles in the Semi‐Hydrogenation of Alkynes (ChemCatChem 1/2021). Issue 1 (7th December 2020) - Staiger, Lena; Kratky, Tim; Günther, Sebastian; Tomanek, Ondrej; Zbořil, Radek; Fischer, Richard W.; Fischer, Roland A.; Cokoja, Mirza
Abstract : The Cover Feature shows a colloidal palladium nanoparticle catalyst for the selective hydrogenation of liquid alkynes. In their Full Paper, L. Staiger et al. show that the reactivity can be tuned by addition of phosphanes. The size and the electronic properties of the phosphanes influence the particle surface and determine both the product selectivity and the catalytic activity. More information can be found in the Full Paper by L. Staiger et al.